Venice : city of pictures - Gayford, Martin (Thames & Hudson, 2023)
Leading art critic Martin Gayford takes us on a visual journey through the past five centuries of the city known as "La Serenissima," the Most Serene. Venice was a major center of art in the Renaissance: the city where the medium of oil on canvas became the norm. Nowhere else has been depicted by so many great painters in so many diverse styles and moods. Nor is the story over. This is a unique and compelling portrait of Venice that will delight lovers of the city and lovers of its art. -- Adapted from book jacket